Directive illocutionary acts as a teaching method relating to status scale dimension in sociopragmatics study - Rosaria Mita Amalia; Jessica Angela Aziz (Proceedings of AICS - Social Sciences, 2017)
Teacher as the main role in learning process tend to communicate with student directly in the classroom. The utterances are categorized as directive illocutionary acts. This can be analyzed by using a sociopragmatics approach. This descriptive research is titled “Directive Illocutionary Acts as Teaching Method Relating to Status Scale Dimension in Sociopragmatics Study”. The object of this research is utterances that contain directive illocutionary acts. The aim of this research is to describe and analyze types of directive illocutionary acts uttered by teachers in the classroom in relation to status scale dimension. The research method used in the research is descriptive.  The writer uses a theory about types of directive illocutionary acts proposed by Searle in Cutting (2002). This research also relates directive illocutionary acts with status scale dimension as proposed by Holmes (2002). Another supporting theory is context theory put forward by McManis, et al. (1987) and direct and indirect speech theory by Yule (1996). The result shows that teachers tend to use commanding, requesting, and forbidding directive illocutionary acts. The dominant status scale dimension is superior in a teacher-student relationship which shows that the teacher has power in the classroom. The contexts that influence the utterance are physical, linguistic, epistemic and social contexts.